International librarianship - Sharma, Ravindra N., 1941-. (New York, NY : Routledge, 2015)
'The International Federation of Library Associations was founded as early as 1927, but in recent years serious academic and practical work on and around international librarianship has flourished as never before. Now, this new title from Routledge's Critical Concepts in Media and Cultural Studies series meets the need for an authoritative collection of major works to make sense of a growing and ever more complex corpus of literature, and to provide a map of the area as it has emerged and developed. Organized in four volumes, it is a landmark collection of foundational and the best cutting-edge scholarship in the field. International Librarianship is fully indexed and has a comprehensive introduction, newly written by the editor, which places the collected material in its historical and intellectual context. It is an essential work of reference and will be welcomed by scholars, librarians, library educators, and students as a vital one-stop research and pedagogic resource'--
Volume 1. Africa - volume 2. The Americas -- volume 3. Asia - volume 4. Europe.
Includes bibliographical references and indexes.
Keywords: International librarianship; Comparative librarianship; Libraries -- Africa; Libraries -- America; Libraries -- Asia; Libraries -- Europe